2011
DOI: 10.1126/scisignal.2002010
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Discovery of ERK2 Substrates Identifies ERK-Mediated Transcriptional Regulation by ETV3

Abstract: The mitogen-activated protein kinase (MAPK) ERK2 is ubiquitously expressed in mammalian tissues and is involved in a wide range of biological processes. Although MAPKs have been intensely studied, identification of their substrates remains challenging. We have optimized a chemical genetic system using analog-sensitive ERK2,a form of ERK2 engineered to utilize an analog of ATP, to tag and isolate ERK2 substrates in vitro. This approach identified 80 proteins phosphorylated by ERK2, 13 of which are known ERK2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 46 publications
5
104
0
Order By: Relevance
“…The cellular components analysis indicated that ERK1 substrates fell into four major categories (Fig. 5A), cytoplasm, nucleus, membrane, and cytoskeleton, a distribution consistent with a previous report (40). In comparison with total human proteome (28,612 proteins) and phosphoproteome (11,479 proteins) having GO annotations from Uniprot and PhosphoSitePlus, respectively, the proportions of cytoplasm, nucleus, and cytoskeleton were significantly increased (Fig.…”
Section: Identifying Direct Substrate Of Erk1 Under the Physiologicalsupporting
confidence: 89%
See 2 more Smart Citations
“…The cellular components analysis indicated that ERK1 substrates fell into four major categories (Fig. 5A), cytoplasm, nucleus, membrane, and cytoskeleton, a distribution consistent with a previous report (40). In comparison with total human proteome (28,612 proteins) and phosphoproteome (11,479 proteins) having GO annotations from Uniprot and PhosphoSitePlus, respectively, the proportions of cytoplasm, nucleus, and cytoskeleton were significantly increased (Fig.…”
Section: Identifying Direct Substrate Of Erk1 Under the Physiologicalsupporting
confidence: 89%
“…4C). We further compared our phosphorylation motif and D domain enrichment with other methods previously reported for in vitro MAPK substrate screening, including ASKA for ERK2 substrates (40) and high throughput in vitro kinase assay for p38 (34). Although three studies shared common features for the consensus motif SP/TP (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous proteins and signaling pathways can influence this cascade through input at its various levels, with activation of Raf by the small GTPase Ras representing the classical pathway. Similarly, the output can be wildly disparate, with over 160 substrates for ERK1 and -2 identified (45)(46)(47) as capable of affecting diverse responses (46). The mechanisms whereby the pathway is able to execute specific responses to different stimuli remain incompletely understood, although the use of scaffolding proteins and distinct pools of kinases in different subcellular locales appears critical (48).…”
Section: Gain-of-function Mutations In the Canonical Transient Receptmentioning
confidence: 99%
“…The maturation of phosphoproteomics techniques based on mass spectrometry (MS) is now allowing the simultaneous quantification of several thousands of phosphorylation sites per experiment, and approaches to derive kinase activity from these large-scale phosphoproteomics datasets have been reported (11)(12)(13)(14). One such approach, named kinase substrate enrichment analysis (KSEA), is based on the premise that, because each phosphorylation site is the result of a kinase's catalytic activity, phosphoproteomic profiling provides a means by which to capture and measure the activities of all kinases expressed in the system under investigation (14).…”
mentioning
confidence: 99%